2011
DOI: 10.3748/wjg.v17.i16.2155
|View full text |Cite
|
Sign up to set email alerts
|

Pure red cell aplasia caused by pegylated interferon-α-2a plus ribavirin in the treatment of chronic hepatitis C

Abstract: Pure red cell aplasia (PRCA) is a rare hematological disorder which is characterized by severe anemia, reticulocytopenia and almost complete absence of erythroid precursors in bone marrow. The pathophysiology of PRCA may be congenital or acquired. To our knowledge, there is only one case report in the English literature of PRCA after pegylated interferon combination therapy for chronic hepatitis C. We report a second case of PRCA after pegylated interferon combination treatment for chronic hepatitis C. The dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Previous studies of PRCA in CHC patients have largely been single case reports pointing to the rarity of the disease [2][3][4][5][6][7][8][9], and studies in populations of dialysis patients have indicated that the prevalence of PRCA could be as low as one case per 10,000 or 100,000 patients [10,12], which is consistent with the upper bound of the 95% CI for the PRCA incidence estimates we report. One hospital-based survey in France identified 2 PRCA cases among 6,630 CHC patients, however both cases were receiving EPO therapy which has been linked to PRCA development through the formation of anti-erythropoietin antibodies [6,7].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies of PRCA in CHC patients have largely been single case reports pointing to the rarity of the disease [2][3][4][5][6][7][8][9], and studies in populations of dialysis patients have indicated that the prevalence of PRCA could be as low as one case per 10,000 or 100,000 patients [10,12], which is consistent with the upper bound of the 95% CI for the PRCA incidence estimates we report. One hospital-based survey in France identified 2 PRCA cases among 6,630 CHC patients, however both cases were receiving EPO therapy which has been linked to PRCA development through the formation of anti-erythropoietin antibodies [6,7].…”
Section: Discussionsupporting
confidence: 89%
“…There have been case reports of PRCA developing in patients undergoing treatment for chronic hepatitis C (CHC) [2][3][4][5][6][7][8]. Limited data are available on the population-based PRCA incidence in patients treated for CHC.…”
Section: Introductionmentioning
confidence: 99%
“…These differ from the typical findings on bone marrow evaluation in PRCA, which are complete or near‐complete absence of erythroid precursors. Although the bone marrow is usually cellular with unaffected hematopoiesis in the nonerythroid cell lines, hypocellularity and a markedly elevated myeloid:erythroid ratio, as in our patient, have been described …”
Section: Discussionsupporting
confidence: 54%
“…Ribavirin accumulation produces depletion of adenosine triphosphate, the deficiency of which sensitizes erythrocytes to oxidative stress and, consequently, to haemolysis [17]. Peginterferon may also contribute to anaemia via bone marrow suppression and, hence, pre-empting compensatory reticulocyte response in these patients [18].…”
Section: Discussionmentioning
confidence: 99%